PEMBANGUNAN POLITIK PENDIDIKAN MENUJU MASYARAKAT BERMARTABAT - Ritaudin, M. Sidi (Analisis: Jurnal Studi Keislaman, 2014)
THE    DEVELOPMENT    OF   POLITICS    OF   EDUCATION TOWARD A DIGNIFIED SOCIETY: The development of politics of education  is currently faced with the development  of science and technology in the communication revolution that gave birth to the global era. The globalization challenge begins when all nations strive to perform ahead of the competition through a reorientation of thought  and reconstruction  of the institutional system.  This paper assumes that Islam is potential to be an independent variable in giving meaning and values to reach a qualified and dignified education. If it is not offset by the enforcement of religious values in the education  system and curriculum, the progress of science, instead of bringing the community with dignity, can even lead to the destruction  of mankind. As a pluralist state, Indonesia is also faced with the demands of unity in cultural diversity. To that end, efforts  must  be taken  to  maximize  multicultural education  by entering a multicultural subject  into the curriculum at all levels.